34th AIAA Applied Aerodynamics Conference 2016
DOI: 10.2514/6.2016-4166
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stall Simulations on a Pitching Finite Wing

Abstract: URANS computations were carried out on a pitching finite wing model using the finite volume solver DLR-TAU. The comparison with the experimental data reveals a good agreement, especially in the region of the first occurrence of stall. Discrepancies are observed in the blade tip region, where the flow in the numerical data shows a stronger separation along with larger hysteresis effects in contrast to the experiment. An investigation with different pitching frequencies revealed a change in the sequence of dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…For example, surface pressure measurements revealed the three-dimensionality of the leading-edge vortex near the wing tip (Gardner et al 2014). In another study, surface pressure measurements at selected locations were combined with the unsteady Reynolds-averaged Navier-Stokes (N-S) computations (Kaufmann, Merz & Gardner 2017), detailing the differences between the wing-tip region and the inboard sections. It was suggested that multiple dynamic stall cells existed over the span.…”
Section: High-aspect-ratio Wingsmentioning
confidence: 99%
“…For example, surface pressure measurements revealed the three-dimensionality of the leading-edge vortex near the wing tip (Gardner et al 2014). In another study, surface pressure measurements at selected locations were combined with the unsteady Reynolds-averaged Navier-Stokes (N-S) computations (Kaufmann, Merz & Gardner 2017), detailing the differences between the wing-tip region and the inboard sections. It was suggested that multiple dynamic stall cells existed over the span.…”
Section: High-aspect-ratio Wingsmentioning
confidence: 99%
“…Moreover, the visualization data has demonstrated that, for the same α, the higher AR wings experience a more developed DSV at the root, which explains the performance data behavior. The pressure and PIV data of previous experiments at higher Rec 23 have also been simulated using numerical approaches 27 . However, simulating wing dynamic stall using URANS was found to predict stall early when compared with experiments 27,28 .…”
Section: Review Of Literaturementioning
confidence: 99%
“…The pressure and PIV data of previous experiments at higher Rec 23 have also been simulated using numerical approaches 27 . However, simulating wing dynamic stall using URANS was found to predict stall early when compared with experiments 27,28 . Furthermore, high-fidelity large-eddy simulations have been applied on pitching finite wings to successfully represent the arch vortex characteristics at transitional Rec 29 , as shown in Fig.…”
Section: Review Of Literaturementioning
confidence: 99%